MENINGKATKAN PENGUASAAN KOSAKATA BAHASA INGGRIS DENGAN MENGGUNAKAN TRADITIONAL SONG DI MADRASAH IBTIDAIYAH JAUHARUL ULUM SITUBONDO - Ach Munawi Husein (STKIP PGRI SITUBONDO, 2019)
English is noticed as one of international languages which is very common to be used by people from different region and country to communicate each other. Nevertheless, the ability to use this language should developed during youth’s school age. Students are often trapped by the very old-fashioned way of learning. They get bored even when they are not learning it. Based on current formal interview with the seventh grade English teacher of MI Jauharul Ulum, the students in class VII had more difficulties in learning English, especially in vocabulary. The students of this class had the lowest motivation in learning and mastering vocabulary. The teacher said that the students often look enthusiastic which is shown by their score in vocabulary which is only 59% of the whole students who got score higher than 70. The research problem of this was “How is the use of Cartoon video able to increase the eighth grade students’ vocabulary mastery at MI Jauharul Ulum in the 2012/2013 academic year? The research objective was intended to find out how the using of cartoon video is able to increase the seventh grade students’ vocabulary mastery at MI Jauharul Ulum in the 2012/2013 academic year. This research applied cartoon video to increase students’ vocabulary mastery. The design of this research was classroom action research. The research subject was the VII grade students at MI Jauharul Ulum in the academic year 2012 /2013. There were two kinds of data applied in this research, primary data were collected using vocabulary test and supporting data were collected using observation checklist. The result of vocabulary test in the first cycle showed that from 32 students there were only 17 (53.13%) of them who got score ≥ 70. This means that the rest of the students did not achieve the target score. In addition, the results of observation in Cycle I revealed that only 65.51% of 32 students actively participated in the teaching and learning process of vocabulary by using Cartoon Video. The rest of the subjects (34.49% of 32 students) were passive in joining the lesson The result of vocabulary test in the second cycle showed that from 32 students, there were only 7 of them who get score ≤ 70, so the rest of them or 78.12% or 25 students got score ≥ 70. This means that more students achieve the target score. The result of observation in Cycle II showed that the students’ active participation improved during the lesson. There were 26 students or 81.25% actively involved in the teaching and learning process of vocabulary mastery through cartoon video. The rest 6 of 38 students were still categorized as passive students. It can be said that the observing in cycle 2 success because more than 75% students active in class. Based on the results above, it could be concluded that the use of cartoon video could improve the seventh grade students’ vocabulary mastery. And it could help the students to identify of nouns, verbs, adjectives and adverbs in a short period and it was worth to be carried for the next vocabulary class.